Foramen Magnum Meningiomas: Still a Big Challenge - Çetintaş, Semih Can; Kaya, Alperen; Tombak, Bülent Kağan; Karaca, Enes; Gürsoy, Salih Alper; Kemerdere, Rahşan; Tanrıverdi, Taner (Cerrahpaşa Medical Journal, 2024)
Objective: Foramen magnum meningiomas (FMMs) are rare but challenging for neurosurgeons to remove because of their anatomic location where vital neuro-vascular structures exist. The difficulties encountered by a neurosurgeon during the surgery and important points during management of complications are underlined, which may help guide young neurosurgeons. Methods: In this report, management of FMMs are provided in 7 patients who underwent surgical treatment between 2012 and 2022. In this small series, 4 women and 3 men were included. Mean age was 54.28 ± 13.61 years with a mean follow-up of 45.71 ± 40.18 months. Results: Although gross total removal was achieved in all patients 3 showed complication (42.8%) during follow-up period. One showed recurrence. Conclusions: Gross total removal in grade 1 FMM does not guarantee total cure, and strict follow-up is mandatory. We conclude that anterior or anterolaterally located FMMs can be safely removed by midline suboccipital subtonsillar approach. More importantly, every possible complication before surgery should be discussed in detail with the patients and/or their next of kin in order to avoid compensation lawsuits, which is a devastating problem among surgeons all over the world. Cite this article as: Çetintaş SC, Kaya A, Tombak BK, et al. Foramen magnum meningiomas: Still a big challenge. Cerrahpaşa Med J. 2024;48(1):59-63.